AS739, AT693 and AU734 antibodies label the spike S protein from SARS-CoV-2 by immunofluorescence - Guilhen, Cyril; Gozlugol, Ezgi; Gosetto, Margaux; Payot, Nina; Khatibi, Khatiba; Jaques, Emma; Schmid, Marie N.; Ollivier, Julien; Vaudano, Alexandre P.; Prodon, François; Volery, Maxime; Poncet, Clément; et al. (Antibody Reports, 2021)
The recombinant antibodies AS739, AT693 and AU734 detect by immunofluorescence the spike S protein from SARS-CoV-2.